Assessing the parameters modulating optical losses of iron oxide nanoparticles under near infrared irradiation. Issue 22 (5th October 2021) - Lozano-Pedraza, Claudia; Plaza-Mayoral, Elena; Espinosa, Ana; Sot, Begoña; Serrano, Aida; Salas, Gorka; Blanco-Andujar, Cristina; Cotin, Geoffrey; Felder-Flesch, Delphine; Begin-Colin, Sylvie; Teran, Francisco J.
Abstract : Heating mediated by iron oxide nanoparticles subjected to near infrared irradiation has recently gained lots of interest. Abstract : Heating mediated by iron oxide nanoparticles subjected to near infrared irradiation has recently gained lots of interest. The high optical loss values reported in combination with the optical technologies already existing in current clinical practices, have made optical heating mediated by iron oxide nanoparticles an attractive choice for treating internal or skin tumors. However, the identification of the relevant parameters and the influence of methodologies for quantifying the optical losses released by iron oxide nanoparticles are not fully clear. Here, we report on a systematic study of different intrinsic (size, shape, crystallinity, and iron oxidation state) and extrinsic (aggregation, concentration, intracellular environment and irradiation conditions) parameters involved in the photothermal conversion of iron oxide nanoparticles under near infrared irradiation. We have probed the temperature increments to determine the specific loss power of iron oxide nanoparticles with different sizes and shapes dispersed in colloidal suspensions or inside live breast cancer cells. Our results underline the relevance of crystal surface defects, aggregation, concentration, magnetite abundance, excitation wavelength and density power on the modulation of the photothermal conversion. Contrary to plasmonic or magnetic losses, no significant influence of nanoparticle size nor shape was observed on the optical losses released by the studied iron oxide nanoparticles. Interestingly, no significant differences of measured temperature increments and specific loss power values were either observed when nanoparticles were inside live cells or in colloidal dispersion. Our findings highlight the advantages of optical heat losses released by iron oxide nanoparticles for therapeutic applications.